Implementation of Restorative Justice in Traffic Accidents by the Ambon Police Traffic Unit - Dewastyana, Jessica; Rodiyah, Rodiyah; Widyawati, Anis (Fox Justi : Jurnal Ilmu Hukum, 2025)
Traffic accidents are a serious problem that not only impacts safety but also raises complex legal and social issues. Traffic accident cases in Indonesia have tended to be handled through formal criminal justice mechanisms that are oriented towards punishment, often failing to provide complete recovery for victims and the community. With the development of the concept of restorative justice, the Indonesian National Police (Polresta Ambon) has begun to implement this approach in case resolution, including at the Ambon Police Department. This study aims to analyze the application of restorative justice in handling traffic accidents by the Ambon Police Department Traffic Unit and identify the obstacles encountered in its implementation. The research method uses a normative-empirical juridical approach with qualitative analysis. Primary data were obtained through interviews with police officers, victims, and perpetrators of traffic accidents, while secondary data were obtained from literature, legal documents, annual reports of the Ambon Police Department, and statistical data from the Central Statistics Agency. The analysis was conducted by linking field findings with the theoretical framework of Restorative Justice (Howard Zehr and John Braithwaite), the theory of justice (Aristotle and John Rawls), and the theory of the Criminal Justice System by Lawrence M. Friedman. The results of the study indicate that the implementation of Restorative Justice in the Ambon Police is carried out through a mediation process involving victims, perpetrators, and community leaders, with a focus on reparation of losses and restoration of social relations. However, its implementation still faces obstacles, both from the aspect of legal substance in the form of a weak regulatory basis, the aspect of legal structure in the form of limited apparatus and infrastructure resources, and the aspect of legal culture in the form of the dominance of the retributive paradigm in society. This study concludes that Restorative Justice is a more humane and just mechanism, but requires strengthening regulations, increasing the capacity of officers, and socialization to the community so that it can be implemented consistently and effectively in Ambon City.